Biological nutrient removal using fixed-bed filters - Li, Huihua. (2008)
In this research, a series of studies of the conventional A2/O process on a fixed-bed filter were carried out. The aim was to evaluate and model the performance of the submerged fixed-bed filter in the treatment of a medium strength synthetic wastewater.